PENGARUH PEMBERIAN PUPUK ORGANIK TERHADAP PERTUMBUHAN JAGUNG (ZEA MAYS L) KECAMATAN AMALI KABUPATEN BONE - ANDI MURNIATI; ISLAWATI ISLAWATI; RAHMAWATI TAHIR (GANEC SWARA, 2023)
Farmers have only used chemical fertilizers so far that lead to a deterioration in soil quality and a reduction in production stability. This is a problem faced by corn farmers in Amali Sub-District, Bone Regency where the production produced is insignificant and the quality is not good. One of the ways to increase the yield of production can be done by improving the cultivation techniques of local varieties. Improvement of cultivation techniques can be achieved by the application of environmentally friendly agricultural systems, such as the use of organic fertilizers that are able to overcome the problems of the soil compaction process and supply macro and micro nutrients into the soil so that their content is sufficient for plant growth and development. The purpose of this study is to determine the effect of applying organic fertilizer on the growth and production of corn crops in Amali Sub-District, Bone Regency. The experimental design used was a randomized block design consisting of 5, namely: control (O), chicken manure fertilizer = 5 tons.ha-1 (O1), cow manure fertilizer = 5 tons.ha-1 (O2), goat manure fertilizer = 5 tons.ha-1 (O3), horse manure fertilizer = 5 tons.ha-1 (O4). Each treatment was replicated 3 times. Based on the results of the study, the treatment of the application of types of organic manure is very significantly influential on each parameter of growth of corn plant yields such as plant height 275.03 cm, number of leaves 275.03, leaf width 15.0b cob diameter 3.87a. cob weight 3.58b pipil weight 138.62 and dry weight 56.87c. The type of treatment of organic fertilizer for animal manure that can provide the highest nutrients is goat manure